2022
DOI: 10.1108/ijtc-01-2022-0009
|View full text |Cite
|
Sign up to set email alerts
|

Food festival research review in contemporary tourism

Abstract: Purpose Food festivals are prevalent for those passionate about food experience globally. More importantly, feedback from food reviewers on mass media platforms has been becoming a critical factor in facilitating the decision-making process of tourists in particular cities. Moreover, stimulating local tourism activities, thanks to food festivals, prove advantageous to the well-being of local habitants. The purpose of this paper is to provide readers with a general overview of food festival research trends in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 97 publications
1
5
0
2
Order By: Relevance
“…In general, the study results shown that local food festival quality has a vital role in improving the image of Egypt as a destination for local food festival tourism, it also increase the revisit intention and raise visitors satisfaction and loyalty rates. Results give the Egyptian food festivals managers the ideal model to deal with visitors needs to retain them for the success of Egypt as a destination for food tourism through visitor satisfaction and loyalty which agreed with (Stylos et al, 2017;Tsai Wang, 2017;Stone et al, 2018;Agyeiwaah et al, 2019;Getz, 2019;Payini et al, 2020;Yang et al, 2020;Van Rousta, 2020;Khoshkam et al, 2022;Pizzichini et al, 2022;Anh et al, 2022;Han et al,2022;Rivera et al, 2022;Chieh & Hee, 2022). Therefore, the hypotheses are accepted and statistically supported.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…In general, the study results shown that local food festival quality has a vital role in improving the image of Egypt as a destination for local food festival tourism, it also increase the revisit intention and raise visitors satisfaction and loyalty rates. Results give the Egyptian food festivals managers the ideal model to deal with visitors needs to retain them for the success of Egypt as a destination for food tourism through visitor satisfaction and loyalty which agreed with (Stylos et al, 2017;Tsai Wang, 2017;Stone et al, 2018;Agyeiwaah et al, 2019;Getz, 2019;Payini et al, 2020;Yang et al, 2020;Van Rousta, 2020;Khoshkam et al, 2022;Pizzichini et al, 2022;Anh et al, 2022;Han et al,2022;Rivera et al, 2022;Chieh & Hee, 2022). Therefore, the hypotheses are accepted and statistically supported.…”
Section: Resultssupporting
confidence: 54%
“…Events when food and meals are produced and consumed, are called "food festivals" (Meretse, Mykletun, & Einarsen, 2016a). As a result, food festivals encourage guests to engage in "holistic, hedonistic involvements" with food by allowing them to try new tastes or preferences in a fun environment (Anh et al, 2022).…”
Section: -1local Food Festivalsmentioning
confidence: 99%
See 1 more Smart Citation
“…6, No. 4 https://is-journal.com діяльності за рахунок гастрономічних фестивалів позитивно позначається на добробуті місцевих жителів [5]. Як указують D. Janiszewska та L. Ossowska, ділова мотивація учасників кулінарних фестивалів не обмежується економічними та маркетинговими аспектами, а включає також і такі мотиви як продовження сімейних традицій і популяризація місцевих традицій та культури [6].…”
Section: Journal Of Innovations and Sustainabilityunclassified
“…Особливостям впливу кулінарних подієвих активностей на розвиток гастрономічного туризму присвячено праці таких авторів: A. T. Tran та ін. [5], D. Janiszewskа, L. Ossowska [6]. Проблеми розробки та проведення ресторанних заходів досліджуються у працях J. R. Walker [7], J. Tum та ін.…”
unclassified